Velocity Shift and Signal-to-Noise Ratio Limits for High-resolution Spectroscopy of Hot Jupiters Using Keck/KPIC - Kevin S. Hong; Luke Finnerty; Michael P. Fitzgerald (The Astronomical Journal)
High-resolution cross-correlation spectroscopy is a technique for detecting the atmospheres of close-in planets using the change in the projected planet velocity over a few hours. To date, this technique has most often been applied to hot Jupiters, which show a large change in velocity on short timescales. Applying this technique to planets with longer orbital periods requires an improved understanding of how the size of the velocity shift and the observational signal-to-noise ratio (SNR) impact detectability. We present grids of simulated Keck/Keck Planet Imager and Characterizer (KPIC) observations of hot Jupiter systems, varying the observed planet velocity shift and SNR, to estimate the minimum thresholds for a successful detection. These simulations realistically model the cross-correlation process, which includes a time-varying telluric spectrum in the simulated data and data detrending via principal component analysis. We test three different planet models based on an ultrahot Jupiter, a classical hot Jupiter, and a metal-rich hot Saturn. For a 6 σ detection suitable for retrieval analysis, we estimate a minimum velocity shift of Δ v _pl  ∼ 30, 50, 60 km s ^−1 , compared to an instrumental resolution of 9 km s ^−1 , and minimum SNR ∼ 370, 800, 1200 for the respective planet models. We find that reported KPIC detections to-date fall above or near the 6 σ limit. These simulations can be efficiently rerun for other planet models and observational parameters, which can be useful in observation planning and detection validation.